Assessing critical mineral occurrence in battery technologies - Camuamba, E.; Damásio, B.; Mendonça, S. (Resources Policy, 2025)
The prevailing geopolitical context has amplified the centrality of core material inputs in the interaction between technological innovation, economic security, and the climate emergency. Battery technologies represent one of the frontiers in this evolving landscape. In this paper, we examine the link between innovation in these technologies and their material inputs, assessed in terms of mineral occurrence in a sample of 33,036 full-text battery patents published from 2000 to 2021. Our findings, which cover 19 battery technologies, show that, on average, battery technologies increasingly rely on critical minerals. The analysis further reveals a rich tapestry of critical minerals beyond the conventional set of key battery minerals, namely lithium. Evidence shows that chromium, gallium, germanium, molybdenum, niobium, phosphate, silicon, tantalum, tellurium, titanium, and zirconium are all growing in relative importance. Analysis of battery technology specialisation profiles and patterns further highlight inventor countries’ critical mineral needs. While the United States has grown more specialised in sodium-ion batteries, China shows a relative advantage in magnesium-ion, sodium-ion and lithium-ion batteries. Significantly, these patterns similarly reflect diverging paradigmatic shifts in battery innovation along a global “North-South” divide. We conclude with a discussion of potential pathways for battery development and propose avenues for further enquiry at the interface of mineral criticality and geoeconomics.